Re-proposing Cultural Based Curriculum System of Tamansiswa as the National Education Foundation in Indonesia - Rizki Ramadhan (Journal of English Language Teaching and Islamic Integration, 2018)
The  problems  faced  by  the  Indonesia  educational  system should  have  been  examined  deeply  as  it  seems  difficult  to  apply  an educational system that can be implemented effectively. This issue can be seen from the number of curriculum changes recently. Considering that problems, developing educational system based on its own nation culture  will  be  considered  to  be  more  effective  in  order  to  build  the characters of the students. By developing Ki Hadjar Dewantara’s idea with  his  system,  the  educational  system  in  Indonesia  will  be  more practical  and  suitable,  since  this  idea  has  been  admitted  as  modern thought or ideas which will give a lot of beneficial for the learners.